2023
DOI: 10.1002/hed.27302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of real‐world outcomes following immunotherapy in recurrent or metastatic head and neck squamous cell carcinoma with outcomes of randomized controlled trials

Abstract: Objectives: Evaluate outcomes of patients with recurrent or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) treated with immunotherapy (IO). Methods: Among patients with R/M HNSCC treated with IO in this retrospective single-institution cohort, Cox regression was used to compare overall survival (OS) for those with platinum-refractory disease and those treated in the first-line setting with OS from KEYNOTE-040/048, respectively. Multivariable Cox regression was used to identify predictors of OS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…Human papillomavirus (HPV) status was not assessed directly in KEYNOTE-048, but p16 status was used as a surrogate for individuals with oropharyngeal tumors: 21–22% of this group of KEYNOTE-048 participants had p16-positive tumors ( 11 ). In the current study, among individuals with a recorded unequivocal HPV status, the proportion of HPV-positive tumors was higher at 69% (oropharynx subtype) and 47% (all subtypes), in line with published reports ( 21 , 28 ). The KEYNOTE-048 population also included more individuals with tumors in the hypopharynx than did the current study population (13–16% versus 5%) ( 11 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Human papillomavirus (HPV) status was not assessed directly in KEYNOTE-048, but p16 status was used as a surrogate for individuals with oropharyngeal tumors: 21–22% of this group of KEYNOTE-048 participants had p16-positive tumors ( 11 ). In the current study, among individuals with a recorded unequivocal HPV status, the proportion of HPV-positive tumors was higher at 69% (oropharynx subtype) and 47% (all subtypes), in line with published reports ( 21 , 28 ). The KEYNOTE-048 population also included more individuals with tumors in the hypopharynx than did the current study population (13–16% versus 5%) ( 11 ).…”
Section: Discussionsupporting
confidence: 92%
“…The current study population was also numerically older than the KEYNOTE-048 population (median age 69 versus 62 years for those receiving pembrolizumab monotherapy and 64 versus 61 years for those receiving pembrolizumab plus chemotherapy), but had a similar proportion of males and of individuals with a history of smoking (~80% in all cases) ( 11 ). Similar demographics have been observed in other R/M HNSCC observational studies and clinical trials ( 19 , 21 , 23 27 ). The proportions of tumors with CPS ≥1 and ≥20 were similar between the current and KEYNOTE-048 populations, although CPS values were not available for almost half of the current study population.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Three other studies have reported the real-world OS for patients receiving pembrolizumab with or without chemotherapy as first-line palliative treatment for HNSCC (two Japanese and one USA population study). All reported similar results to our cohort [25][26][27]. One study, of a Japanese cohort, reported 12-month OS was 51.9% and 58.8% for patients receiving pembrolizumab monotherapy and pembrolizumabchemotherapy, respectively [26].…”
Section: Discussionsupporting
confidence: 83%
“…The second Japanese study did not stratify analyses by treatment type and reported a 12-month OS of 64.5% for all patients receiving any form of pembrolizumab treatment [25]. The third study, of a USA cohort, reported a median OS of 8.8 months and found no significant difference between their observational and reconstructed survival data from the KEYNOTE-048 study [27]. Overall, our data suggest the efficacy of pembrolizumab reported in the KEYNOTE-048 study is reflected in our real-world European population and is similar to other real-world studies in different geographical populations.…”
Section: Discussionmentioning
confidence: 99%